Early iron Age textile tools from the Požega Valley, Croatia - Potrebica, Hrvoje; Kramberger, Julia Katarina Files (Archaeological Textiles Review, 2020)
This paper presents an overview of textile tools from two Early Iron Age sites in northern Croatia. The results of their analysis outline the current state of research into textile production in the Early Iron Age Požega Valley. A total of about 200 finds from both settlement and funerary contexts provide insights into a diverse range of shapes and sizes of loom weights, spindle whorls and spools. These suggest that the site at Kaptol was a settlement where textiles were produced in large numbers. Diversity among the textile tools suggests that woven textiles came in different sizes and were made from yarns of different qualities, reflecting the creativity and innovation of the Hallstatt world. A fragment of a burned wooden beam with three oblique, oval holes, next to a set of loom weights could be the remains of a loom. Spindle whorls and loom weights also appear as grave goods where they might be gender and status indicators with important symbolic value. They may also be related to different levels of skill and specialisation within the process of textile production. If that is the case, the process of textile production itself had symbolic value in Early Iron Age Croatia.